(untitled) (Fiep Bulletin - online, 2012)
Introduction: The accelerated pace of aging in Brazil has created new challenges for society, where age-related changes involve the presence of risk factors and the occurrence of chronic-degenerative diseases, compromising the autonomy of the aged and requiring them to reside in long stay institutions. The early detection of problems and the elaboration of an individualized health care plan are valuable tools to ensure the quality of services rendered to these individuals. Objective: Characterize the institutionalized elderly through global assessment. Methodology: Descriptive and exploratory study conducted in a long stay institution for the elderly (LSIE), with aged individuals selected according to the following criteria: age 60 years or older; good general health; no mental limitations or hearing and speech problems and willing to take part in the study. The research was approved by the Federal University of Rio Grande do Norte (UFRN) Research Ethics Committee (Protocol no. 164/2011). A structured questionnaire on socio-demographic and health aspects was applied. RESULTS: Long stay institutions for the elderly are non-profit philanthropic entities financed by the Municipal Secretariats of Health and Social Assistance, in addition to old age pensions, whose values are established in the Statute of the Elderly. Participants included 300 elderly individuals, 65.1% women, single (44.2%) and widowed (41.8%). The 71-80 age range was the most frequent (41.8%); mean age was 76.6 years; 30.2% had an incomplete elementary education and 25.6% were illiterate. Prior to admission to the institution, 37.2% of the elderly resided with their children. CONCLUSION: Effective measures are needed to establish health-strategies aimed at the institutionalized elderly.